Phylogeography and population genetic structure of red muntjacs: evidence of enigmatic Himalayan red muntjac from India - Singh, Bhim (BMC Ecol Evol, 2021)
BACKGROUND: Identifying factors shaping population genetic structure across continuous landscapes in the context of biogeographic boundaries for lineage diversification has been a challenging goal. The red muntjacs cover a wide range across multiple vegetation types, making the group an excellent model to study South and Southeast Asian biogeography. Therefore, we analysed mitogenomes and microsatellite loci, confirming the number of red muntjac lineages from India, gaining insights into the evolutionary history and phylogeography of red muntjacs. RESULTS: Our results indicated the Northwestern population of red muntjac or the Himalayan red muntjac (M. aureus) in India as genetically diverse and well-structured, with significant genetic differentiation implying a low level of gene flow. The phylogenetic, population genetic structure, as well as species delimitation analyses, confirm the presence of the lineage from Western Himalayan in addition to the previously identified red muntjac lineages. Relatively low genetic diversity was observed in M. aureus compared to M. vaginalis, M. malabaricus and M. muntjak. The M. aureus and M. vaginalis lineages have split during the late Pleistocene, ~ 1.01 million years ago (Mya), making M. aureus the youngest lineage; whereas, M. malabaricus split earlier, ~ 2.2 Mya and appeared as the oldest lineage among red muntjacs. CONCLUSIONS: Pronounced climate fluctuations during the Quaternary period were pivotal in influencing the current spatial distribution of forest-dwelling species’ restriction to Northwestern India. Our finding confirms the distinct Himalayan red muntjac (M. aureus) within the red muntjac group from Northwestern India that should be managed as an Evolutionary Significant Unit (ESU). We recommend a reassessment of the conservation status of red muntjacs for effective conservation and management. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12862-021-01780-2.